Halide-Directed Ligand Engineering Enables Expedient, Controlled and Divergent Syntheses of Diphosphine-Protected Au Nanoclusters - Li, Ying-Zhou; Liu, Zhi-Shuai; Liu, Wen-Yan; Yuan, Zhi-Rui; Yang, Peng-Fei; Xu, Jing; Hao, Fei; Wang, Jin-Gui; Wang, Nian-Xing; Azam, Mohammad; Sun, Di (WILEY-V C H VERLAG GMBH, 2026)
Despite substantial progress in ligand engineering, the efforts in the field of Au nanoclusters have been concentrated almost exclusively on organic ligands. Halides, the most typical auxiliary inorganic ligands widely present in Au clusters, remain virtually unexplored, particularly regarding their effects on cluster construction. Herein, diphosphine Ph2P(CH2)(n)PPh2 (L-n, n = 1-6) is chosen as the co-protecting organic ligands and a comparative analysis on the influential roles of halide ions (Cl-, Br-, I-) in guiding Au cluster synthesis is conducted. A simple yet efficient halide-directed synthetic approach has been developed and a series of Au nanoclusters, including the known [Au-18(L-1)(6)Br-4](2+), [Au-13(L-2)(5)Cl-2](3+) and [Au-8(L-3)(4)Cl-2](2+) that however crystallized in new polymorphic forms, as well as the new reduction-active [Au-18(L-1)(6)Cl-4](2+), luminescence-enhanced [Au-14(L-3)(5)Br-4](2+) and core-isomeric [Au-11(L-n)(4)X-2](+) (n = 4-6; X = Cl, Br, I), are obtained in a more expedient and controllable manner. This work clearly demonstrates the non-negligible roles of halide ions in directing cluster synthesis, and provides an easier access to diverse diphosphine-protected Au nanoclusters. This approach, promising in gram-scale synthesis, is expected to further extend the ligand scope and holds promise for advancing the diversified syntheses of a broader range of ligand-protected metal nanoclusters.